Projected art history : biopics, celebrity culture, and the popularizing of American art - Berger, Doris; Berger, Doris (Ney York [etc.] : Bloomsbury, 2014)
"Biopics on artists have an enormous effect on the popular understanding of what it means to be an artist. Projected Art History highlights the narrative structure and images created in the film genre of biopics, in which the artist's life is being dramatized and embodied by an actor. Doris Berger bridges a gap between art history, film studies and popular culture by investigating how the film genre of biopics adapts written biographies and projects art history for a mass audience. Berger offers an analytical approach by concentrating on the two case studies Basquiat (1996) and Pollock (2000), but also looks at larger issues at play, such as how postwar American art history is being mediated in a popular format such as the biopic. This is the first book to identify the functionality of the biopic film genre and showcase its implication for a popular art history that is projected on the big screen"--
"Examines the biopics of two artists in order to represent and project a form of art history for a mass audience"--
Machine generated contents note: -- Chapter 1. Artist's Biography on Film as Popular Art History Chapter 2. Pollock: A Popular Historiography- Liaisons dangereuses: the filmic staging of Jackson Pollocks - The artistic field- Debates on authorship: from an artist to a star, from a star to an authorChapter 3. Basquiat and Celebrity Culture- A biopic from an artist's perspective - The New Yorker art scene- Author/artist/star: Julian Schnabel's entanglementsChapter 4. Hollywood's Art History/ies: The Relation of Artist Myths and Star LegendsBibliographyFilmographyList of IllustrationsAcknowledgements.
Prijevod djela: Projizierte Kunstgeschichte : Mythen und Images in den Filmbiografien über Jackson Pollock and Jean-Michel Basquiat
Bibliografija: str. 315-343. - Kazalo
Keywords: Basquiat (Motion picture); Pollock (Motion picture); Artists in motion pictures; Biographical films -- United States -- History and criticism; Art and popular culture -- United States; Art, American -- 20th century -- Public opinion; ART / American / General; PERFORMING ARTS / Film & Video / Direction & Production; Basquiat (film); Pollock (film); umjetnost i popularna kultura - SAD; biografski filmovi - SAD; umjetnici na filmu